SURVIVAL OF THE COHORTS OF CARDIAC PATIENTS AND HEALTHY MEN AGED 40–59 YEARS: THE 30-YEAR FOLLOW-UP DATA - V. V. Belov; A. A. Menshchikov (Кардиоваскулярная терапия и профилактика, 2013)
Aim. To assess and compare the survival in four cohorts of 40–59-yearold male residents of the South Ural Region, followed up for 30 years.Material and methods. The four representative samples of 40–59-year-old men residing in the Metallurgichesky district, Chelyabinsk City, were defined: healthy people (H; n=174); patients with essential arterial hypertension (AH; n=149); patients with isolated myocardial infarction (MI; n=198); and patients with both MI and AH (MIAH; n=154). Over the 30-year period of prospective follow-up, the end-point was death from all causes.Results. In H, AH, MI, and MIAH cohorts, aged at baseline 40–59 years, the cumulative 30-year survival was 24,4%, 28,2%, 7,8%, and 19,5%, respectively. There was no significant difference in the survival rates between H and AH, or MI and MIAH cohorts. At the same time, the survival rates were significantly different in the H vs. MI, H vs. MIAH, AH vs. MI, and AH vs. MIAH cohorts. The point estimates of mean and median survival time were significantly different between H and AH vs. MI and MIAH cohorts, but not for H vs. AH, or MI vs. MIAH cohorts.Conclusion. Among 40–59-year-old men, the 30-year survival rates were significantly and negatively affected by MI. However, the survival rates were similar in MIAH and MI cohorts. Essential AH did not markedly affect the cumulative 30-year survival, compared to the H cohort. The data obtained provide annual survival estimates for the 30-year follow-up period among men aged 40–59 years, including healthy individuals and patients with AH and/or MI.